The Use of English Words and Sentences in Japanese Anime Songs (Code Mixing and Language Switching in Japanese Anime Songs) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As the popularity of Japanese Anime increases over time around the world, many anime fans would have realized a unique tendency in the theme songs of their favorite series: the tendency to mix or replace Japanese song lyrics with English words or sentences. The research surrounding the phenomenon of English words usage inside Japanese song lyrics has been done numerous times by numerous persons from different country, institution and generation prior to this article. And thus, this article is written in order to take part in those researches by means of comparing anime theme songs from different ages, the 80s, the 90s and 2000 and above. The purpose is to compare the frequency and tendency of mixing or replacing Japanese lyrics with English words or sentences.